Analisis Peran Bulog dalam Kebijakan Stabilitas Harga Beras pada Kerangka Maqashid Syariah : (Studi Kasus Perum Bulog Kantor Wilayah Sumut) - Said Habibi Harahap; M. Ridwan; Rahmat Daim Harahap (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Rice has a very important role in the life of the Indonesian people in terms of the economic, labor, social, cultural and political aspects of rice issues. This is not a simple matter and is very sensitive so that it must be handled carefully. Therefore, the government gave authority to Perum Bulog, the North Sumatra Regional Office, in this case to continue to carry out its role in maintaining price stability. The discussion of this research relates to the field of Islamic economics in the review of the maqashid sharia framework. So that the approach taken is theories related to price, price fixing, price stability, policy, and maqashid sharia. This research uses descriptive qualitative method. Data collection was carried out by interview, observation, and documentation techniques. The data is analyzed through market operating policy indicators, government rice reserves and warehouse standards. The results of the study show that the role of the North Sumatra Regional Office of Bulog in the rice price stability policy is known based on the policy letter regarding rice contained in the Regulation of the Minister of Trade of the Republic of Indonesia Number 127 of 2018 concerning Management of Government Rice Reserves for Availability of Supply and Price Stability. Bulog's policy relates to maqashid sharia because the North Sumatra regional office of Bulog has a role as well as a policy aimed at the benefit of the ummah, namely dzaruriyat, hajiyyat and tahsiniyat. Factors supporting Perum Bulog Regional Office of North Sumatra in stabilizing rice prices are changes in the market operating season (OP) and quality specifications that must be met. Inhibiting factors are disturbances due to changes in the timing of the harvest season, rising grain prices and phenomena such as natural disasters.